The Role of Retirement Goal Clarity in Mediating Social Support, Future Perspective and The Direct Effect of Financial Literacy, Health Literacy On Retirement Planning - Dhanang Yan Minarhadi; Endah Susilowati; Gideon Setyo (Green Publisher Indonesia, 2024)
The purpose of this study is to determine the influence of financial literacy, health literacy, and social support, as well as a future perspective mediated by clarity of retirement goals on retirement planning. This research was conducted on employees of media companies in the city of Jogjakarta from May to June 2024, with a total of 59 respondents. This research was carried out using quantitative methods and using the Smart PLS-3 test device. The results of this study are that financial literacy, health literacy, and clarity of retirement goals have a positive and significant effect on retirement planning. Social support and future perspectives have no effect on retirement planning. The variable of clarity of retirement goals in this study is proven to be able to mediate the influence of social support and future perspectives on retirement planning.